Detection of Moving Targets using Coherent Optical Frequency Domain Reflectometry - Renner, Esther; Köppel, Max; Schmauß, Bernhard (paper W4.82, 2021)
We present Doppler-corrected position and velocity measurement with a fiber-coupled COFDR system based on the FMCW radar principle for high precision localization applications. A high measurement accuracy and the ability to track targets are demonstrated.<br